Pembentukan Konsep Faktorisasi Aljabar Siswa Berkemampuan Tinggi (Kreano, Jurnal Matematika Kreatif-Inovatif, 2017)
The aim of this qualitative research was to describe construction of algebraic factoring concept of high-ability students using APOS theory. The subjects of the research were high-ability students of SMPN 1 Surakarta and have been selected using purposive sampling. Data retrieved using think aloud method. Based on the findings and discussions, it can be concluded as follows. (1) In action stage: (a) subjects presented their knowledge by using pictures and words, and (b) subtracted the simple algebraic form by classifying the algebraic terms which have the same variables. (2) In process stage: (a) subjects multiplied the binomial using FOIL method, and (b) classified the algebraic terms that have same variables mentally and in the written form when they did the trinomial addition and binomial multiplication. (3) In object stage, subjects factorized the trinomial using procedural method and non-procedural method. (4) In schema stage, subject explained that the factor when multiplied by another factor will produce the factored trinomial and linked all the stages to formed a complete concept of algebraic factoring.